Assessing the Impact of Optimization Measures on Sustainable Water Resource Management in the Guanzhong Area, China - Tang, Bin; Mao, Ruichen; Song, Jinxi; Sun, Haotian; Kong, Feihe; Cheng, Dandong; Gao, Xiangyu (Frontiers in Environmental Science, 2021)
Limited water resources and rapid socioeconomic development pose new challenges to watershed water resource management. By integrating the perspectives of stakeholders and decision-makers, this study aims to identify cases and approaches to achieve sustainable water resources management. It improves and expands the experience of previous project research. The comparative evaluation provides an analytical basis to verify the importance of stakeholder participation in water policy interactions. The results show that if an effective demand management policy is not implemented, the Guanzhong area will not meet water demand in the future. Through the combination of water-saving policies, water transfer projects and other measures, the available water resources will continue into the future. Optimizing management measures, improving the ecological environment, and encouraging stakeholder participation will help change this situation， although supply-side limitations and future uncertainties likely cause unsustainable water. Therefore, decision-makers should pay attention to the application potential of water-saving and other measures to reduce dependence on external water sources. In addition, the three sustainable development decision-making principles identified in this paper can promote the fairness and stability of water policy.